Edukasi Yakis Bacan (Macaca nigra desmarest) Sebagai Bentuk Public Awareness Tentang Konservasi Satwa Liar Di Desa Kokotu, Bacan Kabupaten Halmahera Selatan - Tamnge, Fadila; Mahdi Tamrin; Zulkarnain Riswan Umanahu (Jurnal Pengabdian Masyarakat Hutan, 2025)
Wildlife education is the process of conveying knowledge, understanding, and awareness about wildlife and the importance of conservation to the general public. This activity was carried aout at MTs. Ar-Rayan, Kokotu, Bacan Island, South Halmahera. The aim of this community service is to introduce wildlife, provide information regarding the ecological role and threats faced by Yakis Bacan, and maximize children’s knowledge through interactions with yakis bacan. Community services are carried out in 3 stages, namely (1) education, (2) Counseling, and (3) evaluation. Teaching materials are summarized in the form of infographics and delivered using the storytelling method. Children are taught to recognize Yakis Bacan more closely by drawing, recognizing the shape of the face, body shape, and the difference in hair colour between young and old yakis. Counseling regarding the handling of yakis bacan focuses on first aid when negative interaction occur between humans and yakis. The questionnaire results showed that 83-100% of the children understood the material presented by the team. This shows that students have developed a new understanding of the existance of yakis bacan and their social interactions with humans.